Solar filament impact on 21 January 2005: Geospace consequences. Issue 7 (9th July 2014) - Kozyra, J. U.; Liemohn, M. W.; Cattell, C.; De Zeeuw, D.; Escoubet, C. P.; Evans, D. S.; Fang, X.; Fok, M.‐C.; Frey, H. U.; Gonzalez, W. D.; Hairston, M.; Heelis, R.; et al.
Abstract On 21 January 2005, a moderate magnetic storm produced a number of anomalous features, some seen more typically during superstorms. The aim of this study is to establish the differences in the space environment from what we expect (and normally observe) for a storm of this intensity, which make it behave in some ways like a superstorm. The storm was driven by one of the fastest interplanetary coronal mass ejections in solar cycle 23, containing a piece of the dense erupting solar filament material. The momentum of the massive solar filament caused it to push its way through the flux rope as the interplanetary coronal mass ejection decelerated moving toward 1 AU creating the appearance of an eroded flux rope (see companion paper by Manchester et al. (2014)) and, in this case, limiting the intensity of the resulting geomagnetic storm. On impact, the solar filament further disrupted the partial ring current shielding in existence at the time, creating a brief superfountain in the equatorial ionosphere—an unusual occurrence for a moderate storm. Within 1 h after impact, a cold dense plasma sheet (CDPS) formed out of the filament material. As the interplanetary magnetic field (IMF) rotated from obliquely to more purely northward, the magnetotail transformed from an open to a closed configuration and the CDPS evolved from warmer to cooler temperatures. Plasma sheet densities reached tens per cubic centimeter along the flanks—high enough to inflate the magnetotail in the simulation under northward IMF conditions despite the cool temperatures. Observational evidence for this stretching was provided by a corresponding expansion and intensification of both the auroral oval and ring current precipitation zones linked to magnetotail stretching by field line curvature scattering. Strong Joule heating in the cusps, a by‐product of the CDPS formation process, contributed to an equatorward neutral wind surge that reached low latitudes within 1–2 h and intensified the equatorial ionization anomaly. Understanding the geospace consequences of extremes in density and pressure is important because some of the largest and most damaging space weather events ever observed contained similar intervals of dense solar material.